Economic Structure of Slovak Regions as a Significant Tool of Their Potential Development - Vladimír Hiadlovský; Lenka Hvolková (Barometr Regionalny)
In order to achieve smart, sustainable and inclusive growth, the European Union has set a spectrum of targets via the growth strategy titled ‘Europe 2020’. These targets are elaborated in detail and coordinated in specific national programs and national policies of European Union member states. A detailed analysis of economic structure that influences the situation in a particular region in an outstanding way can be considered a significant activity for the purpose of examination of the current situation and potential development of particular European regions. Research on stronger and weaker economic areas provides the state with important information for decisions on further strategic development of a particular region. The main aim of this paper is to analyse the economic structure of the Slovak Republic and its regions with the help of secondary data. On the basis of this analysis we will determine the possible areas of potential development for specific economic areas in Slovak regions.